Employee Commitment and the Manager-Employee Relationship. An International Work Environment Leadership Model - Grabowski, Gabriel; Stefańska, Magdalena (Zaangażowanie pracowników a relacja menedżer–pracownik. Model przywództwa w międzynarodowym środowisku pracy, 2024)
Aim: The primary objective of this article is to thoroughly explore the issue of employee commitment within the context of the manager-employee relationship and proposing a model of the process of preparing manager to build superior-subordinate relation and form employee commitment in the organisation’s foreign branch. Methodology: The qualitative method of research was implemented in the form of individual in-depth interviews (IDIs) conducted with top managers of internationally operating organisations. Results: Manager-employee relationships evolve. To make the process more satisfactory for both sides, the Leader-Member Exchange (LMX) theory and Positive Organizational Scholarship (POS) concept should be integrated in it. Both concepts are inherently linked to employee management in the international environment. Furthermore, LMX is evolving towards relational leader-member exchange (RLMX). The process of adaptation to a new work environment is connected not only with the cultural, but also personal characteristics of managers and their experience in operating in international organizations. Cultural differences can significantly affect supervisor-superior relation and employee commitment. Nevertheless, it also seems that universal virtues such as respect and trust, shape the dynamism of the process, which consists of stages described in the conceptual model. Implications and recommendations: To reduce or actually minimise the impact of cultural factors on relations between managers and employees, it is necessary to find the appropriate style of leadership and adjust it to each individual. What makes the process successful is the recognition of local employees’ needs as well as the implementation of positive motivation methods. Originality/value: The article aims to contribute to the discourse on LMX and POS in the context of leadership style in international work environment (IWE). Both approaches should be studied in parallel to identify the key determinants of a manager’s success, reaching beyond the cross-cultural dimension. Contrary to the models presented in the literature, the proposed model is based on managers’ perception of the process of adaptation to the host country’s culture.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 3, s. 117-130
Keywords: employee commitment; manager-employee relationship; international work environment; leadership; leader-member exchange; zaangażowanie pracowników; relacja menedżer-pracownik; miedzynarodowe środowisko pracy; przywództwo; LMX; POS